EFEKTIVITAS MEDIA PAPAN FLANEL DALAM MENINGKATKAN KEMAMPUAN PERKALIAN PADA ANAK TUNARUNGU KELAS IV DI SDN. NO. 35 (SDLB) PAINAN UTARA - PRILUSMA ALVARIO (Universitas Negeri Padang, 2016)
Prilusma Alvario. 2011: The Benefit of Flanel Board Media in Increasing the Multiplication Capability to the Deaf Children Class IV in SDN. No. 35 (SDLB) North Painan The research was backgrounded because there are several mistakes with the deaf children solving the multiplication problem between unit and tens. The goal of this research is proving the flane board media to increas the multiplication capability to the deaf children class IV in SDN. No. 35 (SDLB) North Painan. The type of the research that the writer used is quantitative with the experiment method with the Single Subject Research (SSR) and the A-B-A design. The data agregation technique that the writer used is written test that being recorded in the quotation data format with the kind of variabel size uses the number of frequencies the correct answer in the children’s test. According to the data preparation, the mean baseline data is 1(A1) in the amount of 4, mean intervention (B) is 15,7 and the mean baseline 2 (A-2) is 19,2. With the inclination direction to the intervention phase and baseline (A-2) increase. The overlap data at the baseline phase 1 (A-1) to the intervention (B) is 22,2% the overlap data at the intervention (B) to the baseline 2 (A-2) 55,5%. So, it can be concluded that flanel board media is able to increas the multiplication capability between unit and tens to the deaf children class IV in SDN. No. 35 (SDLB) North Painan.